2009 9th International Conference on Electronic Measurement &Amp; Instruments 2009
DOI: 10.1109/icemi.2009.5274710
|View full text |Cite
|
Sign up to set email alerts
|

Development of in-line oil contamination sensor for lubricant of scraper conveyor reducer

Abstract: The development of in-line oil contamination sensor for N320 Lubricant used in scraper conveyor reducer is described. The sensor can detect the NAS contamination level of the lubricant and prompt the replacement of oil when the oil contamination level exceeds the indicator of the exchanging standard of L-CKC industrial closed gear oil. This paper describes the sensor's design requirements, principle of operation, selection of wavelength, mechanical structure design and test calibration. The shortcomings of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The incremental number of particles in each step of degree was double. The level of contamination exceeding level 12 can be determined by using extrapolation [11] as shown in Table 1. However, in this study presents the methodology to experiment the ISO VG100 lubricant due to widespread use of this lubricant in industry such as gearbox and also refers to the metal particles contamination when the number of particles exceeds the maximum allowance of L-CKC industrial closed gear oil standard as provided in Table 2.…”
Section: Measurement Of Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The incremental number of particles in each step of degree was double. The level of contamination exceeding level 12 can be determined by using extrapolation [11] as shown in Table 1. However, in this study presents the methodology to experiment the ISO VG100 lubricant due to widespread use of this lubricant in industry such as gearbox and also refers to the metal particles contamination when the number of particles exceeds the maximum allowance of L-CKC industrial closed gear oil standard as provided in Table 2.…”
Section: Measurement Of Contaminationmentioning
confidence: 99%
“…From [3,4], it was observed that more than 50% of lubricant replacement would be performed even though the lubricant is still in good condition and usable that leads to excessive cost. At present, there are several studies proposing the experiments on lubricant conditions by using several methods such as Ultrasonic measurement of viscosity of liquids, Photoacoustic measurement of liquid viscosity, Measurement of magnetic viscosity in NdFeB, A viscosity and density meter with a magnetically suspended rotor, Capacitive sensor, IR-absorption and optical fiber sensing [5][6][7][8][9][10][11]. This study is an alternative measurement by using magnetic field together with Hall Effect sensor which can be applied for examining the lubricant contamination of metal particles based on NAS 1638 standard with high accuracy and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cost of this developed method is lower than other means of viscosity tests. At present, there are several studies on viscosity and quality tests of industrial lubricants such as Ultrasonic measurement of viscosity of liquids [1], Photoacoustic measurement of liquid viscosity [2], Measurement of magnetic viscosity in NdFeB [3], A viscosity and density meter with a magnetically suspended rotor [4], Capacitive sensor [5], IR-Absorption [6], and Optical fiber sensing [7]. In this study, the measurement methodology was considered only the lubricant viscosity at the temperature of 26 °C and then compared the results to the viscosity classification which is the reference of lubricant characteristic.…”
mentioning
confidence: 99%